INTEGRASI PENGUNGKAPAN LINGKUNGAN, SOSIAL DAN TATA KELOLA DALAM STRATEGI INVESTASI: DAMPAKNYA TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Pelealu, Axel; Rumokoy, Lawren Julio; Tumiwa, Johan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The concept of sustainability has now become a key factor in determining investment performance, particularly stock returns of companies. Companies that are transparent in disclosing policies and achievements related to environmental, social, and governance (ESG) aspects tend to be more attractive to investors, as they are seen as more responsible and stable in managing non-financial risks. Good disclosure of environmental, social, and governance aspects not only enhances the company’s reputation but also strengthens market confidence, which in turn can potentially increase the company’s stock returns. This study aims to analyze the effect of environmental, social, and governance disclosures on the stock returns of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019 to 2023. This study also uses control variables such as company size, leverage ratio, profitability, dividend policy, and inflation rate to ensure that the relationship found between environmental, social, governance disclosures, and investment performance is not influenced by other fundamental factors. The results show that companies with more transparent disclosures on environmental and social aspects tend to show better stock performance, providing positive signals to investors. In addition, good governance disclosures also contribute to improving stock performance. These findings highlight the importance of enhancing the quality of ESG disclosures by companies, as well as the use of ESG information by investors as a consideration in investment decision-making.